Effective population size of broad-snouted caiman (Caiman latirostris) in Brazil: A historical and spatial perspective - Zucoloto, Rodrigo Barban (2021)
Caiman latirostris has a large geographic distribution, that includes Argentina, Bolivia, Brazil, Paraguay, and Uruguay. In Brazil illegal hunting and land use change have caused population decline, relatively well documented in the last three decades. Due to such circumstances, the estimate of species effective population size might help analyze its viability. Single-sample estimator was used to estimate current effective population size (Ne) of broad-snouted caiman populations in representative areas of the species range in Brazil. For the analyzes, genotypes previously obtained were used for subpopulations of the captive colony of the University of São Paulo (USP) and for wild subpopulations. The microsatellites used were Amiμ8, Amiμ11, Amiμ13, Amiμ20, Claμ2, Claμ5, Claμ6, Claμ7, Claμ8, Claμ9 and Claμ10. The 11 loci analyzed produced 18.27 alleles on average. Wild populations showed significant genic and genotypic differentiation among them (p < 0.01). Population structure analyses (Rho-statistics) at Genepop for all loci was 0.376. The effective number of population sizes (Ɵ, the Ne estimator of Migrate-n software) of Caiman latirostris populations from the captive colony at the USP was 117.1 (N = 7) for NRF, 115.2 (N = 4) for Fm1, and 107.5 (N = 4) for Fm5, on the oposite side, the mean value of theta (Ɵ) was 7.7 (N = 51) for the Atlantic SE basin wild population, 9.4 (N = 42) for the Atlantic N/NE basin wild population and 9.6 (N = 91) for the Paraná basin wild population. The mean number of migrants (M of Migrate-n software) varied from 1.7 to 1.9 estimated by migrate-n are comparable to 1.3 estimated by Genepop. It is observed that in most wild population only few adults effectively contribute to genetic variation. The following guidlines are proposed as management actions: (1) an update of population sampling; (2) redefinition, delimitation and conservation of natural habitats; and (3) new conservation genetic studies with special attention to genetic diversity recovery.